Impact of food supplements containing antioxidant on females’ skin of face - Bacevičienė, Rasa; Janušonienė, Laura; Kupčiūnaitė, Ingrida (Slauga. Mokslas ir praktika, 2020)
The skin is the most external human organ, which has direct contact with the environment, therefore, exposed to external stress factors. In order to stop the resulting damage skin cells are constantly involved in tissue regeneration processes, which require a large amount of energy and well-controlled cell metabolism. With increase image, the production of energy and mitochondrial activity decreases, so the cell and tissue function is disrupted and visible structural changes appear that are better known as the signs of skin aging. Nutrition and dietary supplements with antioxidants can protect the skin from aging, it reduces oxidative stress and is influenced by specific biological mechanisms that increase skin protection and regeneration. Objective: To assess skin coloring, luminosity, brightness and transparency, assess skin imperfections, determine the subjective skin freshness before and after supplementation. The study included 9 (37 - 51 years) women, which after evaluation of phenotype, their skin type was determined as II-IV, they were not allergic and did not have any increased sensitivity to anyone of the dietary supplement ingredients. Skin “radiance” was used to evaluate C.L.B.T.™ methodology to assess the different facial characteristics: the coloring, luminosity, brightness and transparency. This evaluation was based on a visual analysis of the following seven descriptors, clearly defined by consensus: a red-pink, olive, beige, and light-pink skin coloring (C), as well as the luminosity (L), brightness (B), and transparency (T) of each subject’s facial skin. The scoring of perceived skin descriptor was made with the help of structured and analogical scales. The results were registered before and after 8 weeks. Conclusion. Food supplements significantly reduced the women’s facial skin redness and increased brightness and luminosity. Food supplements significantly reduced the dark circles under the eyes, colour and relief, skin redness, skin spots and global skin imperfection score.